Co-implantation of oxygen vacancy and well-dispersed Cu cocatalyst into TiO2 nanoparticles for promoting solar-to-hydrogen evolution. (8th January 2023) - Qiu, Pei; Lu, Mengjie; Cheng, Gang; Li, Wei; Liu, Lijun; Xiong, Jinyan
Abstract: Semiconductor photocatalysis serves a green technique to convert solar energy to sustainable hydrogen energy through water splitting. TiO2 has attracting increasing interest and much effort has been paid on addressing the suffered drawbacks of solar energy utilization limitation and electron-hole recombination. In this work, simultaneously involving of oxygen vacancy and Cu into TiO2 nanoparticles has been achieved through self-reduction of Cu2 O and self-transformation of Ti-precursor from Cu2 O@Ti-precursor in ethylene glycol-water medium. The Cu@TiO2-x hybrids show improved photocatalytic H2 production, and the Cu@TiO2-x -1% sample has H2 evolution rate of 7218.8 μmol g −1 h −1, which is 2.1 times higher than that of TiO2-x . It is proposed that the involving of metallic copper and oxygen vacancy by this solvothermal approach can enhance light absorption, promote electron-hole pairs separation and charge transfer, and increase active sites of TiO2 nanoparticles, resulting in synergetic effect for hydrogen production improvement. Highlights: Oxygen vacancy and Cu cocatalyst were simultaneously embedded into TiO2 . The Cu@TiO2-x -1% sample has the highest photocatalytic hydrogen evolution rate of 7218.8 μmol g −1 h −1 . The oxygen vacancy in TiO2 prohibited the rapid recombination of electron-hole pairs. The Schottky junction at the Cu@TiO2 interface improved charge transfer. Multiple charge transfer channels were built in the Cu@TiO2-x hybrid.